Market interactions, trust and reciprocity - Choi, Ginny Seung; Storr, Virgil Henry (PloS one, 2020)
Trust is a key ingredient of almost all market interactions. Much of the literature on the relationship between trust and market activity, however, has focused on how trust facilitates market activity rather than on how market activity affects trust. In this study, however, we investigate whether market interactions can affect the subsequent trusting and reciprocating behavior of former trading partners. Additionally, we explore the effect of personal and impersonal exchange on the trusting and reciprocating behavior of former trading partners. We find experimental evidence that suggests that positive and negative market interactions can affect such behavior. Further, we find that past market dealings only affect the trusting and reciprocating behavior of subjects who participated in an experimental market where exchanges were more personal, but did not affect trust and reciprocity between trading partners who participated in an experimental market where exchanges were more impersonal. In the market where exchanges are more personal, people exhibit higher levels of trust and reciprocity to trading partners with whom they have mostly positive market interactions than with whom they have mostly negative market interactions. However, in the market where exchanges are more impersonal, people exhibit the same levels of trust and reciprocity to trading partners regardless of the nature of their previous market interactions.